Human rights dialogue with Arab States : argumentation patterns of authoritarian regimes as a challenge for a values-based foreign policy - Grimm, Jannis; Roll, Stephan (2023)
Zusammenfassung: Germany is being met with rejection from the governments of Arab states when it calls for human rights to be respected. If those being addressed do not outright refuse to engage in dialogue, they usually rely on four patterns of argumentation to ward off corresponding demands: (1) the human rights situation in their own country is already improving, but the process still needs time, (2) concerns such as economic development and the fight against terrorism should take precedence over civil rights, (3) human rights are a Western construct and ignore the cultural characteristics of the societies being addressed, and (4) Western human rights policy is characterised by double standards. German officials should be aware of these objections and counter them proactively when they engage in dialogue on human rights. Above all, the German government should engage the accusations of cultural imperialism and double standards, not least because these beliefs are widespread among the populations of Arab countries. To counterbalance these accusations, the universal claim of human rights should be emphasised more strongly – especially in the context of a feminist foreign policy. Additionally, self-interests that potentially undermine the proclaimed values-based approach should be identified and articulated more clearly. Finally, the dialogue on human rights should be underpinned by concrete measures